Social Rights and International Development: Global Legal Standards for the Post-2015 Development Agenda - Kaltenborn, Markus (Springer, 2016)
This book addresses practitioners in development cooperation as well as scientists and students who are interested in the interaction of human rights and development issues. In the practice of development cooperation, linking poverty reduction programs with human rights is mainly achieved using so-called “Rights-based Approaches to Development.” In this context the right to an adequate standard of living (including access to food, water and housing), the right to health and the right to social security are of particular importance – human rights that will play a key role in the design of the Post-2015 Development Agenda, which is currently being negotiated as a framework to succeed the Millennium Development Goals. The book provides an overview of the main international legal standards that are relevant for the protection of social rights, while also analyzing the content of those rights. Moreover, it informs readers on the current debates surrounding the extraterritorial obligations of donor countries and the duties of transnational corporations and international organizations (e.g. the World Bank and WTO) with regard to the implementation of social rights in the Global South.